2020
DOI: 10.1002/aocs.12368
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids in Commercial Krill Oils: Concentrations, Compositions, and Implications for Oxidative Stability

Abstract: The concentrations and pro‐oxidative effects of free fatty acids in commercial krill oil are not well defined. We now report that krill oil free fatty acids account for 2–13% of total lipids in commercial krill oil (n = 8) that these compounds are enriched in eicosapentaenoic acid (+7.1%) and docosahexaenoic acid (+6.3%) relative to whole oils; and that this composition make them highly pro‐oxidizing in marine triacylglycerol oils, but not in krill oil, which derives oxidative stability from both its phospholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Generally, high free fatty acids cause hydrolytic rancidity and affect the quality of oils, thus, the amount of free fatty acids is considered as a quality parameter for oils [41]. The acceptable range of free fatty acids in commercially available krill oils is suggested to be up to 2 wt% [42], while the extracted SO contained much lower amounts of free fatty acids confirming superior quality.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, high free fatty acids cause hydrolytic rancidity and affect the quality of oils, thus, the amount of free fatty acids is considered as a quality parameter for oils [41]. The acceptable range of free fatty acids in commercially available krill oils is suggested to be up to 2 wt% [42], while the extracted SO contained much lower amounts of free fatty acids confirming superior quality.…”
Section: Discussionmentioning
confidence: 99%
“…FAME profiles were measured as described previously. 5 Briefly, samples (10 mg) were weighed into screw-top reaction tubes (10 mL), adding acetyl chloride (2 mL, 2% v/v in dry methanol/toluene 10:1), and heating (90 °C for 60 min). After cooling, FAME were recovered from the reaction mixture by adding hexane (3.8 mL), mixing well, and collecting the upper hexane/toluene layer for analysis by gas chromatography mass spectrometry (GC-MS).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…2,6,7 Unlike fish oil, krill oil also contains astaxanthin, a naturally occurring ketocarotenoid with potent antioxidant activity, which gives these oils a distinctive red color and protects their PUFA-containing molecules from oxidation. 5 For decades fatty acid concentrations (including EPA and DHA) have been routinely measured by gas chromatography− mass spectrometry (GC-MS). 8−9 This method can simultaneously quantitate dozens of individual fatty acids accurately and precisely, but oils must first be derivitised to more volatile formats (e.g., methyl esters) and separated chromatographically over time.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have found that high levels of FFA reduces the oxidative stability of vegetable and marine oils by acting as a prooxidant 40,41 . The high levels of FFA may have resulted in a reduction in the observed amount of PUFA in our samples, as the rate of oxidation is positively correlated with the degree of unsaturation.…”
Section: Lipid Class Compositionmentioning
confidence: 99%